Emerging Methodologies and Humanized Theoretical Learning: An Explanatory Study with Colombian University Students - Velásquez, Oscar Andrés Vargas; Jenny, Romero Borre; Murillo, Hernán Javier Guzmán (Journal of Posthumanism, 2025)
This work is based on the conviction that university teaching must cultivate mind and sensitivity at the same time. With this in mind, a non-experimental explanatory study was designed that involved all 819 students enrolled in a Psychology program in Montería (Córdoba, Colombia), who answered a Likert-type questionnaire previously validated by experts and with reliability α = 0.75. The statistical analysis, carried out in SPSS 20, showed that the incorporation of emerging methodologies – in particular Scrum and Kanban adapted to classroom projects, gamified activities and student-centred dynamics – was associated with appreciable increases in students’ perception of flexibility, autonomy and motivation, in addition to facilitating the integration between theory and practice. In light of these findings, guidelines are proposed that combine conceptual rigor with experiential experiences to train professionals in the area capable of working with ethical responsibility and social empathy. In summary, the evidence suggests that emerging methodologies not only enrich theoretical learning, but also humanize the educational experience by promoting collaborative, reflective and sensitive environments to the needs of the contemporary context.